Integrating ethics into accounting curriculum: overview from Malaysian accounting educators - Noor Lela Ahmad, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Ethics in accounting education become a vital issue after a spate of recent accounting scandals that involves multinational companies such as Enron, Sunbeam, Waste Management, and Worldcom, and Malaysian companies such as Transmille Group and Southern Bank Bhd. This paper examines the findings of an in-depth study that analysed the perception of five Malaysian accounting educators on the question of integrating ethics into accounting curriculum. Utilising the constant comparison method comprising purposive sampling, in-depth interviews, direct observation and documentary analysis the study explored the importance of incorporating ethics into the curriculum, its problems and the factors that encouraged accounting educator to integrate ethics in their teaching. The findings revealed that while accounting educators believed in the integration of ethics in accounting curriculum and the nurturing of ethical accountants, there are certain barriers such as time constraints, lack of knowledge, skills and competency in the task, and lack of reference materials to be used in teaching accounting ethics.